Reframing rest: the importance of sleep and interactive education for children and adolescents - White, Elizabeth, author; Meyer, Carolyn, advisor; Ivie, Kenny, committee member (Colorado State University. Libraries, 2026)
Sleep is a critical physiological process that lays the foundation for health and prosperity. Regulated by the circadian rhythm and sleep drive, it consists of four stages that cycle throughout the night, each serving distinct physiological functions. Various areas of the brain work in concert to coordinate sleep, including the hypothalamus, pineal gland, basal forebrain, brainstem, and amygdala. Because sleep affects every system in the body, its quality and duration profoundly influence both mental and physical health, contributing to various risks spanning from cardiovascular disease to depression. In today’s world of efficiency, technology, and early school start times, sleep is increasingly deprioritized—especially among adolescents, 77% of whom experience sleep deprivation. By leveraging the effectiveness of interactive and visual learning, sleep education for children can be used to combat sleep deprivation among adolescents. After researching the anatomy, mechanisms, and importance of sleep, as well as the science behind youth learning, I developed a project to educate children of Fort Collins and encourage early development of positive sleep habits.
Keywords: sleep; learning; youth